Impact of Gender Equality on Sustainable Development - H. Yasmeen Sultana; Fathimath Roobiya Nu; M. Abual Jamal (International Journal of Rural and Regional Development, 2024)
In order to achieve social and institutional change that promotes equitable and growth-oriented sustainable development, gender equality is regarded as a crucial component. Men's and women's differences show up in every aspect of development. The following areas show the greatest disparities: social attitudes, gender stereotyping, economic development, participation in public life and policymaking, violence against women, health, and education. Gender equality is one of the most sophisticated and rapidly growing social movements of the twenty-first century. The sustainable development goals, if gender is not taken into consideration, represent a critical approach to building a more sustainable and better future for all. Gender equality is necessary for sustainable development because it ensures that men and women have equal access to opportunities and resources. Therefore, there is a link between gender equality and attempts to advance sustainable development. Its foundations include democracy, the rule of law, and observance of basic rights including equality of opportunity and freedom. Sustainability cannot exist unless there is equity in the distribution process. In order to implement, contribute to, and reap the benefits of sustainable development, girls and women are essential. As a result, developing sustainable routes and eliminating gender inequality are urgent problems. This study examines the relationship between gender equality and sustainable development objectives
Keywords: Gender inequality; gender development index; gender empowerment measure; gender gap; sustainable development